Profile of Mathematical Representation Ability to Solve Mechanical Wave Matter Physics Problems - Dita Fitriani; I Ketut Mahardika; Bambang Supriadi (PILLAR OF PHYSICS EDUCATION, 2023)
Physical Science develops through a series of scientific processes and cannot be understood by memorization, but rather requires understanding concepts so physicists use various forms of representation. The mathematical representation approach is often used in physics learning. This study aims to examine more deeply the ability of mathematical representation of students of SMA Negeri 1 Cluring class XI MIPA in solving mechanical wave problems. The research method used is descriptive quantitative. The data collection technique used is a written test consisting of five description questions based on mathematical representations of mechanical wave material, interviews, observations, and documentation. The results of the study obtained the average mathematical representation ability of students in solving mechanical wave matter physics problems thanks to the "excellent" category of 68.89%, the "good" category of 9.29%, the "good enough" category of 8.69%, the "not good" category of 1.90%, and 11.24% of students categorized as fail in solving physics problems using mathematical representations of mechanical wave matter.